Beyond the bids: Lessons from farmers' reflections on Vickrey auctions of sweetpotato vines in Rwanda - Kilwinger, Fleur B.M.; Spielman, David J.; Almekinders, Conny J.M.; Rajendran, Srinivasulu; van Dam, Ynte K. (Elsevier, 2025)
Context The use of high-quality seed can significantly enhance nutrition, food security, poverty alleviation, and climate change adaptation in rural farming communities. Economic valuation methods can be used to assess farmers' demand for such seed. However, the reproductive biology of seed and the social and economic institutions surrounding their production and exchange vary widely across crops and regions.